2015
DOI: 10.1016/j.neuropharm.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Lighting up G protein-coupled purinergic receptors with engineered fluorescent ligands

Abstract: The use of G protein-coupled receptors fluorescent ligands is undergoing continuous expansion. In line with this, fluorescent agonists and antagonists of high affinity for G protein-coupled adenosine and P2Y receptors have been shown to be useful pharmacological probe compounds. Fluorescent ligands for A1R, A2AR, and A3R (adenosine receptors) and P2Y2R, P2Y4R, P2Y6R, and P2Y14R (nucleotide receptors) have been reported. Such ligands have been successfully applied to drug discovery and to GPCR characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 84 publications
0
36
0
Order By: Relevance
“…In fact, the literature reports several examples of fluorescent ligands for all four AR subtypes. A very comprehensive review on fluorescent ligands for ARs was reported by Kozma et al [67] and extended to some newer derivatives by another two reviews published in 2014 and 2015 [68,69]. Thus, here the most representative fluorescent ligands are reported among with the new fluorescent ligands for the ARs reported in the literature from 2015 to now.…”
Section: Fluorescent Ligandsmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, the literature reports several examples of fluorescent ligands for all four AR subtypes. A very comprehensive review on fluorescent ligands for ARs was reported by Kozma et al [67] and extended to some newer derivatives by another two reviews published in 2014 and 2015 [68,69]. Thus, here the most representative fluorescent ligands are reported among with the new fluorescent ligands for the ARs reported in the literature from 2015 to now.…”
Section: Fluorescent Ligandsmentioning
confidence: 77%
“…Ciruela and coworkers developed another member of this class of A 2A antagonists, where they introduced dye 467 directly to the hydroxyl group of SCH442416 ( Figure 13). SCH442416Dy647 (47) was employed to undoubtedly demonstrate the presence of A 2A /D 2 oligomers in native tissues of rat striatum, which is essential information for designing new therapies for Parkinson's disease [69,100]. The pyrazolo [4,3-e] [1,2,4]triazolo [1,5-c]pyrimidine scaffold was also functionalized at the 5 position, leaving the 7 position unsubstituted and inserting a methyl group at the 8 position: substitutions that should shift selectivity towards the A 3 AR [102].…”
Section: Fluorescent Ligandsmentioning
confidence: 99%
“…We successfully enhanced their A 2A AR affinity compared to known fluorescent A 2A AR ligands. 15 Conjugates 11 and 12 were potent and selective antagonist probes for the A 2A AR, but 12 was more promising for characterization of the hA 2A AR in whole cells by flow cytometry. Molecular modeling suggested that the fluorophore of 11 interacted with hydrophobic regions between TMs.…”
Section: Discussionmentioning
confidence: 99%
“…Various fluorescent probes have been developed over the past few years for characterizing ARs, 13 15 and their use in fluorescence polarization (FP), fluorescence resonance energy transfer (FRET) and flow cytometry (FCM) has been proven to be feasible. Moreover, these ligands can provide a better understanding of receptor location, function and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As far as receptor-ligand systems are concerned, binding of ad rug candidate is characterized by competitiveb inding experiments in which am olecule of interest (L) competes with al abeled reference ligand (L*), the affinity of which toward the receptor is known.I ns uch pharmacological assays,d etermining the concentrationo fL *i nc ell culture samples requires veryhigh measurement sensitivity.Asaconsequence, radioactivity remains the method of choice for studying receptor-ligand interactions. [3] However,r adioactivity has many constraints linked to radioelement manipulationa nd storage, thus strongly limiting HTS applicability.I nt his context, we aim at developing an on-radioactive technology that relies on highly sensitive detection and quantification by matrix-assisted laser desorptioni onization mass spectrometry (MALDI-MS).In attempts to avoid the use of radioactivity,awide variety of techniques have been developed for characterizing targetligand binding interactions.T his objective was achieved through several approaches, some requiring labeling, such as fluorescencer esonancee nergy transfer (FRET) [4] and fluorescence polarization (FP), [5] as well as label-free methods such as surfacep lasmon resonance (SPR). [6] However,s uch techniques suffer from disadvantages such as directly affecting the receptor-ligand interaction, high background interference, or requirements of fastidious processing.…”
mentioning
confidence: 99%